Trading in books in time of plague (1522) - Angela Nuovo; Laura Pani (JLIS.it, 2021)
By analysing some letters sent in 1522 by the agent Bernardo d’Asola to the Venetian publisher and bookseller Giovanni Bartolomeo Gabiano, the article aims to reconstruct ways of organising book distribution at the Recanati and Lanciano fairs. The trade fairs, as evidenced by the letters, are particularly unfortunate because of the plague that affected various areas of Italy in 1522. An edition of Bernardo’s significant letter of 17 October 1522 sent from Recanati follows the text.